Assessment of noise levels in work areas at the Polokwane Platinum Smelter, South Africa - Mdaka, Themba Cyprian (University of Limpopo, 2015)
Objective This study assesses whether noise levels above legal limits of 85 dB(A) that can result in noise-induced hearing loss are present in areas where employees are supposed to work and to verify that such areas are demarcated as noise zones at the Polokwane Platinum Smelter. Background and motivation Excessive noise is a global health hazard with considerable social and physiological impact, including the development of noise-induced hearing loss (NIHL). Noise is a major hazard in many workplaces. It is estimated that more than 30 million workers (almost 1 in 10) are exposed to unsafe noise in their work places. NIHL is the second most self-reported occupational illness or injury in the United States. Amongst miners, more than 90% of the population reports hearing problems by the age of 55 years. Noise exposure is prevalent in construction, foundries, agriculture, transport, industry and mining-related activities. The prevalence of NIHL has not changed much in the past two decades. Therefore, a hearing conservation programme is an important issue in the smelter as certain areas are denoted as noise areas. Study design A cross-sectional study design with a group of utility workers at the Polokwane Platinum Smelter, as the experimental group, and a group of undergraduate Bachelor of Science students at the University of Limpopo (Turfloop Campus) served as a control group. Method A sound level meter was used to measure the noise levels where the utility group performs their technical work. Data were analysed using the Statistical Package for the Social Sciences (SPSS) computer program. Results The average noise measured in various locations of the Polokwane Platinum Smelter was between 62.6 dB(A) and 105.1 dB(A). The results indicated that workers at the Polokwane Platinum Smelter are over exposed to noise in certain work areas if they work eight hours in the area. Areas where the average noise level was above noise rating limit of 85 dB(A) were demarcated as noise zones as an additional protective measure. Employees also use hearing protective devices, when they are working in noise zones, to control personal noise exposure. This is in accordance with the Occupational Health and Safety Act No. 85 of 1993 as amended eleventh edition (OHS Act 85/93). Conclusion In the present study, noise levels in certain areas exceeded the noise rating limit of 85 dB(A). However such areas are clearly demarcated as noise areas and employees accessing those area must wear earmuffs or earplugs. Possibilities of employees developing hearing loss overtime exist, if employees work for eight hours or longer in demarcated areas and do not adhere to the existing Hearing Conservation Program (HCP) implemented at the Polokwane Platinum Smelter. Noise levels at the Polokwane Platinum Smelter should be monitored regularly.
Thesis (M.Sc (Physiology)) --University of Limpopo, 2015
Keywords: Noise; Work areas; Platinum smelter; 363.119622; Noise-Pollution -- South Africa.; Mineral industries -- South Africa -- Environmental aspects; Noise -- Measurement